Indole pyruvate decarboxylase gene regulates the auxin synthesis pathway in rice by interacting with the indole-3-acetic acid–amido synthetase gene, promoting root hair development under cadmium stress - Shah, Gulmeena; Fiaz, Sajid; Attia, Kotb A.; Khan, Naeem; Jamil, Muhammad; Abbas, Adeel; Yang, Seung Hwan; Jumin, Tu (Frontiers in Plant Science, 2022)
Auxin phyto-hormone acts as a regulator in plant growth and development and is also a key character in plant defense and pathogenesis. Majority of Pathogenic species are involved in producing IAA by different pathways. In our previous studies, we showed that microbial communities (Bacillus Cereus) not only strengthen plant-microbe interaction but it also promotes plant growth by improving nitrogen availability and enhance nutrient and water uptake results in reducing the hazardous effect of Cd in soil. In PGPR biosynthesis, IAA mainly proceeds through intermediate IPyA followed by the IPDC Precursor gene by Tryptophan dependent pathway. Due to secretion of bacterial Auxin, expression of certain genes indirectly controlled many processes in the plant; current studies were designed to investigate responsible genes in plant and PGPR for interaction and Production of IAA, and lateral root development due to the involvement of several metabolic pathways. Studies revealed that GH3-2 interacts with endogenous IAA in a homeostasis manner without directly providing IAA; expression lines of the IPDC precursor gene showed a 40% increase in lateral roots in the host plant. B. Cereus normalizes the oxidative stress caused by Cd due to O2 ̇ ͞ and H2O2 accumulation in osaux1 lines. In root tip, histo-chemical staining with Hoesht-33242 and Propidium iodide showed a higher death rate towards the osaux1 mutant line. Furthermore, inoculation of B. cereus in OAUX1 expression increase GUS expression, indicating that bacterial species have a positive role in Auxin regulation. Despite the effect of B. cereus on IAA biosynthesis and transport, IAA genes showed down-regulation in the transcript level of osaux1-3 compared to WT. Thus the overall picture of our work showed that B. cereus increased the root hairs (RH) development in rice by interacting with IAA synthetase genes.